Poly(butylene terephthalate/carbon nanotubes nanocomposites. Part II. Structure and properties - Piesowicz, E.; Irska, I.; Bryll, K.; Gawdzińska, K.; Bratychak, M. (Polimery, 2021)
The properties of poly(butylene terephthalate) (PBT) based nanocomposites filled with MWCNTs (multiwall carbon nanotubes) and epoxy peroxide functionalized MWCNTs (EpMWCNTs) have been studied. The analysis was focused on the influence of EpMWCNTs on the phase structure, thermal, mechanical and electrical properties of synthesized materials. Functionalized MWCNTs were observed to be highly dispersed and well integrated in the PBT matrix. Obtained results demonstrate that the incorporation of EpMWCNTs into the PBT matrix yields materials of enhanced thermo-oxidative stability. It was found that the crystallization temperature for all the obtained nanocomposites is slightly higher than that for the neat polymer. Increasing the concentration of nanofiller in both MWCNT and EpMWCNT systems improved the mechanical properties Young's modulus, tensile strength and fracture strain. The electrical conductivity of nanocomposites decreased due to the functionalization of MWCNTs with epoxy peroxide.